Survey of Avian Fauna in and around Kurukshetra, Haryana, India - Gupta, Sanjeev K.; Kumar, Parmesh (Indian Forester, 2009)
Kurukshetra, a place of great historical and religious importance, 160 km North of Delhi on National Highway No. 1 (NH1) was surveyed for avian fauna from August, 2005 to July, 2008. Owing to different types of habitats, it harbours rich avian fauna. A checklist of 110 bird species is presented along with information on status and habitat.